2011
DOI: 10.2147/ijn.s16653
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biodistribution and biological impact of injected carbon nanotubes using magnetic resonance techniques

Abstract: International audienceSingle-walled carbon nanotubes (SWCNT) hold promise for applications as contrast agents and target delivery carriers in the field of nanomedicine. When administered in vivo, their biodistribution and pharmacological profile needs to be fully characterized. The tissue distribution of carbon nanotubes and their potential impact on metabolism depend on their shape, coating, and metallic impurities. Because standard radiolabeled or fluorescentlylabeled pharmaceuticals are not well suited for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 34 publications
1
37
0
1
Order By: Relevance
“…In a following study, it was found that purified SWNTs with 2% impurities and functionalized SWNTs with 0.7% impurities did not yield a statistically appreciable signals, thus confirming a threshold value of 10% Fe impurities required for significant MRI contrast. 76 Importantly, this study corroborates that 2% Fe, as impurities, can be tolerated in vivo, as no acute toxicological effect was observed in the liver using high-resolution magic angle spinning and quantitative real-time polymerase chain reaction analysis.…”
supporting
confidence: 77%
“…In a following study, it was found that purified SWNTs with 2% impurities and functionalized SWNTs with 0.7% impurities did not yield a statistically appreciable signals, thus confirming a threshold value of 10% Fe impurities required for significant MRI contrast. 76 Importantly, this study corroborates that 2% Fe, as impurities, can be tolerated in vivo, as no acute toxicological effect was observed in the liver using high-resolution magic angle spinning and quantitative real-time polymerase chain reaction analysis.…”
supporting
confidence: 77%
“…New techniques for tissue clearing may allow for a more refined observation of particle distribution in the near future (Susaki and Ueda, 2016). For in vivo imaging of particle distribution magnetic resonance imaging (MRI) may be used (Al Faraj et al, 2011).…”
Section: Testing Methodsmentioning
confidence: 99%
“…The "holy grail" in CNTs-mediated targeted cancer phototherapy 36 is to deliver high doses of active bionanomolecules to tumor sites for maximum treatment efficacy while minimizing side effects to normal organs 58 ( Figure 4). …”
Section: In Vivo Photothermal Ablation Of Tumors Mediated By Cntsmentioning
confidence: 99%